The Relationship Between Serum β-Carotene Concentrations and Reported Dietary β-Carotene Intakes Is Moderated by BMI in U.S. Adults. (7th June 2021) - Crusan, Ambria; Demmer, Ryan; Reicks, Marla; Raatz, Susan
Abstract: Objectives: Serum β-carotene (BC) concentrations are not reflective of dietary BC status as serum concentrations can vary as a result of intake, lifestyle factors, adiposity, and physiological factors related to digestion and absorption. Longitudinal studies have shown a positive relationship between serum carotenoids and dietary BC intake, but the role of body mass index (BMI), as a surrogate for adiposity, in predicting serum BC concentrations is not well understood. The primary objective was to determine the role of BMI in the association between reported dietary BC intakes and serum BC concentrations. Methods: Relationships between serum BC and reported dietary intake of BC were estimated using data from National Health and Nutrition Examination Surveys (NHANES)/What We Eat in America (WWEIA) survey 2003–2006 for 2580 male and non-pregnant female participants aged 20–85 years in the United States (US). The distributions of reported dietary and serum BC concentrations were skewed, therefore natural log (ln) was used to transform the data. Multivariable linear regression estimated serum BC concentrations based on reported dietary intake of BC adjusted for age, sex, race/ethnicity. Additional models were run by BMI category (normal, overweight, obesity class I, obesity class II, and obesity class III). Results: Mean serum BC concentrations were 14.59 ± 0.1 μg/dL, BMI was 27.80 ± 0.1 kg/m 2, and reported dietary intakes of BC were 828.82 ± 0.06 μg. A moderate association was present between serum BC and reported dietary BC intake, r = 0.30, P < 0.0001. When assessed according to BMI categories, the multivariable linear model shows attenuation of the β coefficient from 0.21 to 0.16, 0.12, 0.12, and 0.13 for the respective BMI categories. Conclusions: In a representative sample of U.S. adults, there was a moderate association present between reported dietary BC intakes and serum BC concentrations. Additionally, the relationship between serum BC concentrations and reported dietary BC intakes was moderated by BMI, suggesting individuals with an increased BMI and/or body fat percentage may have a greater risk of low serum BC concentrations despite dietary BC intake. Funding Sources: N/A.